PERANAN RISET DAN PENINGKATAN KETERAMPILAN ARSITEK LANSKAP DALAM MENGHADAPI PENERAPAN KONSEP GREEN BUILDING - Lestari Suryandari; Yodi Danusastro (Jurnal Lanskap Indonesia, 2011)
Implementation of Green building concept is expected to promote the progress of industrial property and the role of the experts whose involved in the process, including Landscape Architects. Instead benchmark valuation increasing over time, with the current version of the assessment in Indonesia, the role of landscape design can contribute up to 12% of the total value. Criteria that require the involvement of Landscape Architects primarily related to the basic green areas poin, site landscaping poin, and water efficient landscaping poin. Poin and the benchmark is still potential to increase along with the relevance rating systemically so that will indirectly addvalue to other criteria such as energy and overalls Thermal Transfer Value (OTTV). This is not related, but not directly with developing standards in landscape design. The development of this standard requires further research, such as Indonesianregional plant data, technologies and methods of irrigation, landscape maintenance techniques, and the reconciliation of the standardization of regulations which spread as the various standards that are adopted from another country. By increasing the quality and quantity of research in the field of landscape architecture and landscape plants, is expected to improve the quality of green building practices toward higher standardsand still have its own characteristics of Indonesia.